Effects of Kesawan District in West Medan Structure on Individual Behavior (International Journal of Architecture and Urbanism, 2022)
This paper discusses the Influence of Kesawan Medan Barat Village Structure on Individual Behavior. Behavior can be interpreted as human actions or activities that have a very wide range. Behavior is also interpreted as a person's response or reaction to external stimuli, one of which is the environment. Humans have an individual personalities as well as social beings, living in a collectivity society. Humans are also the center of the environment and at the same time part of the environment. Every human activity, especially those in urban areas, usually inseparable from the use of space. In accordance with the characteristics of the problems studied, this paper is included in descriptive research. Descriptive research is research on a problem in the form of the latest facts from a population which includes activities to assess attitudes or opinions towards individuals which are carried out to determine the value of an independent variable, either one variable or more, without making comparisons or connecting with other variables. In this paper, information is collected related to the structure of the city which is the object of research, then analyzed to provide an overview of the relationship between the influence of urban structure on individual behavior